OPTIMIZATION OF RISKS OF THE INVESTMENT PORTFOLIO OF ART OBJECTS ACCORDING TO THE LEVEL OF FINANCIAL SECURITY OF ART INVESTING IN THE LOCAL ART MARKET - Daryna Momot (Сучасний стан наукових досліджень та технологій в промисловості)
The article is devoted to the study of theoretical and methodological principles and development of practical recommendations for optimizing the risks of the investment portfolio of art objects according to the level of financial security of art investing in the local market. The subject of the study is a set of theoretical, methodological and practical aspects for optimizing the risks of the investment portfolio of art objects according to the level of financial security of art investing in the local market. The purpose of the article is to develop theoretical and methodological provisions and substantiate practical recommendations for optimizing the risks of the investment portfolio of art objects according to the level of financial security of art investing in the local market. Objectives: to investigate and systematize the conceptual and categorical apparatus of financial security of art-investment; to develop a methodical approach to assessing the level of investment attractiveness of an art object according to the level of financial security of art investing; to offer analytical and applied support for optimizing the risks of the investment portfolio of art objects according to the level of financial security of art investing in the local art market. During the research the following methods were used: abstract-logical analysis, theoretical generalization, system and statistical analysis, system and statistical analysis, economic-mathematical methods, graphical method. The essence and genesis of the concept of investment as an economic category in the context of the development of the history of economic thought are determined, on the basis of which the specific features of the investment process are generalized, the concept of art-investment is defined. Analytical and applied support for minimizing the risks of the investment portfolio of art objects at the level of financial security of art investment in the local art market and its testing on the example of the author's investment portfolio of art objects of contemporary Ukrainian artists. Conclusions. Analytical and applied support for minimizing the risks of the investment portfolio of art objects by the level of financial security of art investing in the local art market was developed. It allows to determine the investment potential of the art object by the components of financial security of art investment by the parameters of the internal environment based on the assessment of the multiplier to assess the investment attractiveness of art objects; to establish the priority of investing in art object as part of the investment portfolio; to position each art object on the matrix taking into account the emotional effect of ownership of the art object for the investor.